Direct growth of thick AlN layers on nanopatterned Si substrates by cantilever epitaxy. Issue 4 (April 2017) - Demir, İlkay; Robin, Yoann; McClintock, Ryan; Elagoz, Sezai; Zekentes, Konstantinos; Razeghi, Manijeh
Abstract : Here, Demir et al. (Article No.1600363 ) demonstrate the pulsed atomic layer epitaxy AlN layers that have been grown on a 200 nm period of nano‐patterned Si (111) substrates by a cantilever epitaxy via MOCVD, and compared with AlN layers grown by a maskless lateral epitaxial overgrowth (LEO) on micro‐patterned Si (111) substrates. The material quality of 5‐10 μm thick AlN grown by LEO is comparable to that of the much thinner layers (2 μm) grown by cantilever epitaxy on the nano‐patterned substrates. Back emission ultra violet light emitting diodes (UV LEDs) were fabricated by flip chip bonding to patterned AlN heat sinks, followed by a complete Si (111) substrate removal, demonstrating a peak pulsed power of ~0.7 mW at 344 nm peak emission wave‐length. Additionally, this study features the first demonstration of UV LEDs on nano‐patterned Si substrates.